2020
DOI: 10.21303/2461-4262.2020.001399
|View full text |Cite
|
Sign up to set email alerts
|

Research of Change in Fraction Composition of Vehicle Gasoline in the Modification of Its Biodethanol in the Cavitation Field

Abstract: The influence of bioethanol content and parameters of the cavitation field on the quality indicators of motor gasolines: volatility and octane number is studied. Studying the effect of bioethanol and cavitation treatment of bioethanol-gasoline mixture will make it possible to produce automotive fuels for different climatic zones, or winter (summer) versions of gasolines. The use of bioethanol and cavitation treatment of a bioethanol-gasoline mixture affect the fractional composition of motor gasoline and its v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Work [14] reports the composition of an alcohol-gasoline mixture before and after cavitation treatment, as well as suggests a path of chemical transformations, which explains the presence of ethers in a bioethanol-gasoline mixture. A similar scheme can be offered to explain the presence of ethers and olefins in the isopropanol-gas-condensate mixture.…”
Section: Analysis Of Experimental Data and Comparison Of Results Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Work [14] reports the composition of an alcohol-gasoline mixture before and after cavitation treatment, as well as suggests a path of chemical transformations, which explains the presence of ethers in a bioethanol-gasoline mixture. A similar scheme can be offered to explain the presence of ethers and olefins in the isopropanol-gas-condensate mixture.…”
Section: Analysis Of Experimental Data and Comparison Of Results Withmentioning
confidence: 99%
“…However, the cited research does not provide any theory that could relate the time of cavitation to the intensity of the mechanochemical activation of gasoline and does not consider the effect of cavitation on gasoline when adding alcohols. Another work [14] studied the impact of cavitation treatment on the characteristics of the gasoline fraction modified with bioethanol. It is shown that cavitation can significantly improve the anti-detonation characteristics of alcohol-gasoline mixtures; however, no experimental data are given to investigate the effect of cavitation in the modification of gasoline with other single-atomic alcohols.…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
“…Finding the peculiarities of the technological process found its justification and deep analysis in the work [7,8]. It is shown that the impossibility of a direct solution to the problem is related to the fundamental features of the object, namely, a large number of technological parameters, the change of each of which will shift the extremum of concentration.…”
Section: Engineeringmentioning
confidence: 99%
“…In [7], a traditional method is shown, which is effective, but the overall performance is limited by several disadvantages. The first drawback is that approximately 30 % of the total cost of producing nitric acid is ammonia as a feedstock, which limits the economic output from this feedstock source and includes environmental concerns.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%